(untitled) (Physical Education, Health and Social Sciences, 2025)
Budd-Chiari syndrome (BCS) is a hepatic disease of rare occurrence characterized by hepatic venous outflow obstruction, traditionally presenting with hepatomegaly, ascites, and liver dysfunction. Gastrointestinal manifestations like diarrhea are underdiagnosed and rare. Here we report a case of a 21-year-old male patient with the presenting complaints of abdominal pain, ascites, jaundice, and chronic diarrhea. Imaging showed hepatic venous outflow obstruction and laboratory findings showed a hypercoagulable state with positive lupus anticoagulant and factor V Leiden mutation. The patient was treated by having a Transjugular Intrahepatic Portosystemic Shunt (TIPS) procedure, with resolution of the diarrhea. Recurrence of the symptoms after shunt blockage and resolution after TIPS had been reevaluated only further established the association between hepatic congestion and symptoms. This situation does point to a possible pathophysiologic connection between hepatic congestion and abnormal gut motility and it does emphasize the necessity of heightened surveillance and investigation for gastrointestinal symptoms in BCS.